(untitled) (Proceedings of Faculty of Civil Engineering, 2025)
This study examines the pivotal role of construction infrastructure in the development of tourism, using the City of Opatija as a case study. Through an analysis of geographic location, urban planning factors, tourist assets and events, as well as historical tourism, the research focuses on the importance of infrastructure projects for a destination’s attractiveness and competitiveness. By analyzing hotel accommodation, projects under construction, spatial planning and the significance of tourist infrastructure, the study provides insight into how Opatija leverages its construction assets to meet tourist demands year‑ round. Emphasis is placed on maintaining a balance between preserving cultural heritage and adapting to contemporary trends. The analysis demonstrates the importance of continuous investment in both developing and maintaining construction infrastructure so that the tourist city of Opatija retains its status as an attractive tourist destination and stimulates the local community’s economic development. The paper lays the groundwork for further research on the impact of construction infrastructure on tourism and suggests a need for ongoing monitoring and adjustment of urban planning and projects to ensure the destination’s sustainability and competitiveness.